2019
DOI: 10.1101/791814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alcohol induces mitochondrial fragmentation and stress responses to maintain normal muscle function in Caenorhabditis elegans

Abstract: AbstractsChronic excessive ethanol consumption produces distinct toxic and adverse effects on different tissues. In skeletal muscle ethanol causes alcoholic myopathy characterized by myofiber atrophy and loss of muscle strength. Alcoholic myopathy is more prevalent than all inherited muscle diseases combined. Current evidence indicates that ethanol directly impairs muscle organization and function. However, the underlying mechanism by which ethanol causes its toxicity to muscle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…These data reveal that alcohol has a greater impact on cellular mitochondrial fission, which coincides with several previous research studies conducted on liver tissue and in Caenorhabditis elegans. 64,65 On the other hand, the removal of injured mitochondria through autophagic sequestration and lysosomal degradation by mitophagy is essential to the maintenance of cardiomyocyte homeostasis in physiological and pathological conditions. 56 Although limited evidence is currently available with regard to the involvement of mitophagy during the pathogenesis of ACM, several studies have shown that chronic ethanol administration induced a disruption of autophagosomal processing and lysosomal function and led to the accumulation of autophagosomes in the liver tissue.…”
Section: Papermentioning
confidence: 99%
“…These data reveal that alcohol has a greater impact on cellular mitochondrial fission, which coincides with several previous research studies conducted on liver tissue and in Caenorhabditis elegans. 64,65 On the other hand, the removal of injured mitochondria through autophagic sequestration and lysosomal degradation by mitophagy is essential to the maintenance of cardiomyocyte homeostasis in physiological and pathological conditions. 56 Although limited evidence is currently available with regard to the involvement of mitophagy during the pathogenesis of ACM, several studies have shown that chronic ethanol administration induced a disruption of autophagosomal processing and lysosomal function and led to the accumulation of autophagosomes in the liver tissue.…”
Section: Papermentioning
confidence: 99%
“…Previous studies have shown that mitochondria serve a role in the development of rare neuromuscular diseases, such as Duchenne and Becker muscular dystrophy (20,21). Mitochondrial dysfunction affects muscle function, leading to atrophy (22). Muscle weakness is the primary symptom of MG.…”
Section: Mitochondrial Dynamics and Biogenesis Indicators May Serve A...mentioning
confidence: 99%
“…Thrashing assay. Detailed protocol was described previously (Oh et al, 2020). Age-matched adult animals (24 h post-L4) were placed in 1 ml M9 buffer on an unseeded nematode growth media plate.…”
Section: Microscopy and Image Analysismentioning
confidence: 99%